Structure-based specificity mapping of secreted aspartic proteases of Candida parapsilosis, Candida albicans, and Candida tropicalis using peptidomimetic inhibitors and homology modeling - Majer, Filip; Pavlíčková, Libuše; Majer, Pavel; Hradilek, Martin; Dolejší, Elena; Hrušková-Heidingsfeldová, Olga; Pichová, Iva (Biological chemistry, 2006)
Secreted aspartic proteases (Saps) of pathogenic Candida spp. represent a specific target for antifungal drug development. We synthesized a series of peptidomimetic inhibitors with different isosteric groups and modifications at individual positions and tested them with purified Saps from C. albicans (Sap2p), C. tropicalis (Sapt1p), and C. parapsilosis (Sapp1p). The kinetic parameters indicated that all three proteases prefer binding of inhibitors containing bulky hydrophobic residues between positions P3 and P3'. The most divergent specificity was found for Sapp1p. The sequence alignment of Sap2p, Sapt1p, and Sapp1p, and homology modeling of Sapp1p with the crystal structure of Sapt1p and the complex of Sap2p with a peptidomimetic inhibitor showed that the overall folds of Sap2p, Sapt1p, and Sapp1p are similar. However, the N- and C-terminal loops formed by disulfide bonds between residues 47-53 and 258-292 are significantly shorter in Sapp1p, and a unique insertion following Tyr 129 in Sapp1p results in the formation of a loop that can interact with inhibitor residues. These Sapp1p structural differences might lead to its altered susceptibility to inhibition.
Keywords: financování organizované; molekulární konformace; aspartátové endopeptidasy; sekvenční homologie aminokyselin; Protein Structure, Tertiary; Sequence Homology, Amino Acid; Substrate Specificity; sekvence aminokyselin; Protease Inhibitors; Structure-Activity Relationship; terciární struktura proteinů; Molecular Sequence Data; Aspartic Acid Endopeptidases; inhibitory proteas; Stereoisomerism; stereoizomerie; Amino Acid Sequence; Molecular Conformation; Models, Molecular; Financing, Organized; molekulární sekvence - údaje; molekulární modely; vztahy mezi strukturou a aktivitou; Candida; Isoenzymes; substrátová specifita; izoenzymy